The model of prioritization of services for efficient usage of multiservice network resources - Klymash, Mychailo; Beshley, Mykola; Koval, Valeriy (Видавництво Львівської політехніки, 2012)
In this paper the method of prioritization of services of multiservice network has been created. The simulation statistical model of the priority service of multiservice traffic with classifier of priorities has been proposed. The parameters and structure of multiservice telecommunication network have been analized on the basis of the simulation model.
Keywords: parameters QoS; multiservice traffic; Differentiated Services Code Point; buffer; simulation model